The Use of Learning Videos in Order to Increase Student Motivation and Learning Outcomes During The COVID-19 Pandemic - Dewi Hernawati; Asep Bayu Dani Nandiyanto; Nazeri Muhammad (ASEAN Journal of Science and Engineering Education, 2021)
The COVID-19 pandemic affects almost all areas of life, one of which is education. In the field of education, the learning process during the pandemic has turned into Distance Learning. Distance learning which is carried out online has many obstacles in its implementation. The learning media used are very influential in the success of online learning during a pandemic. Online learning requires creative learning media so that students don't feel bored and stay motivated in learning. The purpose of this study was to determine the motivation and learning outcomes of students in sixth grade elementary school Kamarung 1, Indonesia on building space material after online learning was carried out using video as a learning media during the COVID-19 pandemic. The subjects of this study were sixth grade students of elementary school Kamarung 1, Indonesia in the 2020/2021 academic year. Data collection techniques through pretest and postest. The analysis technique used is descriptive qualitative. The results showed that the use of video learning media accompanied by learning assistance could improve the learning outcomes of sixth grade students at elementary school Kamarung 1, Indonesia on building space material.